Analisis Pengaruh Kepuasan, Kepercayaan Merek, Loyalitas Merek terhadap Ekuitas Merek : Studi pada Sepeda Motor Suzuki di Kota Yogyakarta - , ANDIN DWI YULIANI; , Widya Paramita, S.E., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Developing a strong brand name is the goal of every company because the brand is an asset for the company, which required a good relationship between the brand and the consumer. This research aims to examine the effect of satisfaction on brand trust, the effect of brand trust on brand loyalty, the effect of brand loyalty on brand equity and the mediating effects of brand trust on the relationship between satisfaction and brand loyalty in the products of Suzuki motorcycles. This research was conducted using a quantitative approach with a survey method and data was collected using questionnaire which were distributed to 150 respondents in Yogyakarta. Sampling was obtained by using non-probability sampling with a purposive sampling technique that required a judgment sampling. The analytical methods used are quantitative by using simple regression analysis and mediation test to see the effect of brand trust as mediation on the relationship between satisfaction and brand loyalty The results show that satisfaction has a positive effect on brand trust, brand trust has a positive effect on brand loyalty, and brand loyalty has a positive effect on brand equity. In addition, brand trust has a role of partial mediator in relationship of satisfaction and brand loyalty.